2008
DOI: 10.1001/jama.299.20.2423
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Susceptibility to Cancer

Abstract: Context-Continuing advances in genotyping technologies and the inclusion of DNA collection in observational studies have resulted in an increasing number of genetic association studies.Objective-To evaluate the overall progress and contribution of candidate gene association studies to current understanding of the genetic susceptibility to cancer.Data Sources-We systematically examined the results of meta-and pooled analyses for genetic polymorphisms and cancer risk published through March 2008.Study Selection-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
101
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 366 publications
(103 citation statements)
references
References 126 publications
2
101
0
Order By: Relevance
“…In addition to the well-defined, highly penetrant modifications to genes such as BRCA1 and BRCA2, which are only observed in a limited number of cases, certain common, low-penetrance variations have been identified in other genes potentially implicated in BC (Dong et al, 2008). Recently, several genome-wide association studies (GWAS; Antoniou et al, 2008;Garcia-Closas et al, 2008;Mcinerney et al, 2009;Latif et al, 2010) have revealed multiple BC-associated loci, of which the majority are single nucleotide polymorphisms (SNPs).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the well-defined, highly penetrant modifications to genes such as BRCA1 and BRCA2, which are only observed in a limited number of cases, certain common, low-penetrance variations have been identified in other genes potentially implicated in BC (Dong et al, 2008). Recently, several genome-wide association studies (GWAS; Antoniou et al, 2008;Garcia-Closas et al, 2008;Mcinerney et al, 2009;Latif et al, 2010) have revealed multiple BC-associated loci, of which the majority are single nucleotide polymorphisms (SNPs).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies reported that the IL-17 gene is expressed by Th17 cells and modifies chronic inflammation, and SNPs in IL-17 may alter gene expression, thus changing protein function and contributing to cancer risk (Park et al, 2005;Dong et al, 2008). Here, we performed a hospital-based case-control study to assess whether the IL-17 rs2275913 genetic variation could influence susceptibility to gastric cancer, and we found that IL-17 rs2275913 genetic variations appear to be associated with an elevated risk of gastric cancer in a Chinese population.…”
Section: Discussionmentioning
confidence: 99%
“…Wacholder et al (2004) suggested that the statistical power be estimated based on the ability to detect an OR of 1.5, when the alpha level was equal to the observed P value. Dong et al (2008) found that for small ORs, an OR of 1.5 could be too conservative; so both ORs of 1.5 and 1.2 were used. FPRP values less than 0.2 indicate that the association is still significant for a given level of prior probability.…”
Section: Methodsmentioning
confidence: 99%